The global persistence of work from home - Cevat Giray Aksoy; Jose Maria Barrero; Nicholas Bloom; Steven J. Davis; Mathias Dolls; Pablo Zarate (Proceedings of the National Academy of Sciences, 2025)
Work from home (WFH) surged worldwide during the COVID-19 pandemic, then partially receded as the pandemic subsided. Using our Global Survey of Working Arrangements covering dozens of countries, we find that average WFH rates among college-educated employees stabilized after 2022. The average number of WFH days per week is steady at roughly 1 d per week globally from 2023 through early 2025. Cross-country variation persists: WFH is about twice as common in advanced English-speaking economies as in much of Asia. These results show how the pandemic-driven shift to remote work has persisted and reached a new equilibrium with implications for urban economies, workforce flexibility, and future research on labor markets.